Brand as a driving force for small and micro businesses in China - Xiaoping, Jiang (2017)
In China, small and micro businesses account for 94.15% of the main market players and contribute significantly to social employment opportunities. However, small and micro businesses are facing pressures of intense market competition. Considering that a good brand image may be a key to enhance the competitiveness of these companies this research analyses the influence of brand driving force in the internal level of management of Chinese small and micro firms. In light of the Report of Development of Small and Micro Enterprises in China, we conducted a survey to small and micro businesses in the laser industry and electromechanical retail industry. With the statistical software IBM SPSS 19.0 and AMOS, we tested the scale “brand driving force”. Based on the analysis of reliability, construct validity, discriminate validity and convergent validity, we confirmed that the theoretical model of enterprise brand driving force is applicable, reasonable and effective. As a result, we concluded that the brand is a driving force for the enterprise management improvement. The empirical research, combining qualitative with quantitative analysis, led to the following main findings: 1) The brand-oriented development of small and micro businesses is determined by brand naming, brand positioning and brand equity, which are the core dimension of brand metaphorical force, brand stabilizing force and brand capital force, respectively. 2) The development of a model to test the brand driving force of small and micro enterprises has been put forward. It consists of three dimensions—metaphorical force, stabilizing force and capital force of brand. A comprehensive and systematic explanation of the source of brand driving force has been given and checked by formal data. 3) It confirms that the “brand driving force” is the core motive power for enterprise management level promotion”. Based on the data analysis of the small and micro enterprises in industry and retail sector, empirical tests have been conducted on measuring scale, mechanism model and evaluation model. If applied, the evaluation model of brand driving force can reflect the degree of the driving force in the form of score, thus pointing out the direction for small and micro enterprises management level promotion.